Food, blood and little white stones: A study of ritual in the Icelandic Viking Age hall - Jakob Orri Jónsson 1987- (2014)
The study of ancient beliefs and rituals is a complex thing that has troubled scholars through the centuries. People have always wondered about the religions, beliefs and traditions of other people throughout time. Scholars as far back as the time of Tacitus and the Roman Empire have described the religious and ritual practices of foreign cultures, however, such accounts tend to be coloured by the writer's own religious background, the political climate of the time and bias in which texts survive and in what form. Similar problems surround oral accounts. The advantage of archaeology in this case is, to use the words of Ann-Britt Falk "that you get to analyse what people really did, not what they were supposed to do." The aim of this thesis is to look at the archaeology of the Icelandic Viking Age hall and draw out signs of ritual as theorized from a combination of historical, folkloric, ethnographic and archaeological material. It is my hope that using these sources it will be possible to identify heathen rituals in the archaeological record of Iceland. While leaving out other archaeological remains does potentially exclude large amounts of evidence for ritual, the focus this does afford allows a more in depth look at the subject matter than might otherwise be possible.